Analisis Tracer Study Alumni Program Studi S1 Ilmu Komputer UIN Sumatera Utara - Rina Afriani Sitorus; Dimas Arya; Buyung Satrio Dasopang Buyung Satrio Dasopang; Ilka Zufria Ilka Zufria (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This tracer study collects information and analyzes the profiles of alumni of the Computer Science undergraduate study program at UIN North Sumatra. The method used in this research is a descriptive method that will describe the alumni profile. Data collection in this research used an online survey method by distributing a questionnaire consisting of several questions as the main instrument. The aim of this research is to evaluate the effectiveness of the UIN North Sumatra Computer Science undergraduate study program in providing education and preparing graduates who are competent and ready to work and to evaluate the quality of education received by alumni during the study period. This research analyzes the suitability of alumni to market needs by distributing questionnaires to assess the Cumulative Achievement Index obtained by alumni at the end of their studies, the length of the alumni's study period, the length of the alumni's waiting period to get a job, the suitability of the alumni's field of work and the scope of alumni's work. The results of this research can provide a better understanding of how study programs can produce graduates who are competent and ready to face challenges in the world of work and can also provide recommendations for institutions to improve the quality of education and relevance of the curriculum to better suit the needs of the current world of work. Keywords: tracer study, alumni, graduates, balance of work fields, Computer Science